Thermophysical properties and thermal performance evaluation of multiwalled carbon nanotube-based organic phase change materials using T-History method - Yadav, Chandrmani; Sahoo, Rashmi Rekha (John Wiley and Sons Ltd, 2022)
Experimental studies have been carried out to evaluate the thermophysical properties and thermal performance of thermal energy storage (TES) systems. The TES system was filled with 0%-0.025% vol. fractions multiwalled carbon nanotubes (MWCNT)-based lauric acid (LA), paraffin wax (PW), and stearic acid (SA) nanoparticle-enhanced phase change materials (NEPCMs). The T-History method has been used to explore the thermophysical parameters, i.e., solid-liquid specific heat capacity, solid-liquid thermal conductivity, and heat of fusion. Results revealed that the solid thermal conductivity of the 0.02% MWCNT in lauric acid, paraffin wax, and stearic acid increased by 37.8%, 24.4%, and 13.5% than LA, PW, and SA phase change materials (PCMs), respectively. Also, an improvement in liquefying and solidification time has been observed for 0.02% vol. fraction MWCNT-based NEPCMs. However, the dimensionless numbers justified that the combined conduction and natural convection effect occurred in the PCMs/NEPCMs thermal energy storage. The coefficient and rate of heat transfer have been compared among 0%-0.025% vol. fraction of MWCNT-based pure lauric acid, paraffin wax, and stearic acid PCMs/NEPCMs. Also, the maximum heat transfer rate for 0.02% MWCNT in lauric acid, paraffin wax, and stearic acid NEPCMs has been increased by 61.16%, 87%, and 26.4%, respectively, compared to LA, PW, and SA phase change materials. Hence, the 0.02% MWCNT/PW-NEPCM-based TES system has higher performance than the mentioned TES systems.
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: Heat storage; Latent heat; Multiwalled carbon nanotubes (MWCN); Paraffins; Saturated fatty acids; Solidification; Specific heat; Stearic acid; Thermal conductivity; Thermal energy; Heat transfer rate; Lauric acid; Melting-solidification time; Multi-walled-carbon-nanotubes; Multiwall carbon nanotube; Organic phase; Solid/liquid; Solidification time; Thermal energy storage systems; Thermal performance evaluations; Phase change materials